Germination behavior of Jatropha curcas L. after different imbibition times - Lozano, F. (2017)
Jatropha curcas is an important specie for production of biofuel. The specie can survive and produce fruits and seeds even in drought condition. For an adequate establishment in the field is necessary that seeds have a good quality in vigor and viability. In this study, we evaluated the seed water relation with different imbibition times, in deionized water, from 0 to 24 hours. Imbibed seeds were sown in polyethylene trays with 1,200 g of river sand. The germination was recorded every day for 25 days. Seeds with at least 10 mm radicle on the soil surface was considered as germinated. To determinate seed water content (SWC), 10 seeds were weighed in fresh (SFW), turgid (STW) and dry weight (SDW) at 105°C for 24 hours. After 24 hours of imbibition our results show a decrease in the germination rate from 85% to 47%, and an increase of the mean germination time from 4.8 to 7.1 days. The initial moisture of the seed used in this experiment was about 8% and after 24 hours of imbibition, the SWC was around 60%. The initial low moisture in the seeds produce imbibition damage because the tissue hydration takes place in a not controlled way so that the reconstruction of internal structures of the cells and organelles were affected. According to the PCA analysis the seed germination had a negative correlation with the imbibition time (r = -0.72, p < 0.05) and with the electrical conductive (r = -0.88, p < 0.05), variables related to the seed vigor. This study suggests that electrical conductivity may be useful in J. curcas for vigor test and their seeds do not need previously water imbibition to improve germination from seeds with initial moisture less than 8%.